Anaerobic Spondylodiscitis due to Fusobacterium Species: A Case Report Review of the Literature - Tiffany N. Latta; Aimee L. Mandapat; Joseph P. Myers (Case Reports in Infectious Diseases)
Spondylodiscitis caused by Fusobacterium species is rare. Most cases of spontaneous spondylodiscitis are caused by Staphylococcus aureus and most postoperative cases are caused by Staphylococcus aureus or coagulase-negative staphylococci. Escherichia coli is the most common Gram-negative organism causing spondylodiscitis. Fusobacterium species are unusual causes for anaerobic spondylodiscitis. We report the case of a patient with spontaneous L2-L3 spondylodiscitis, vertebral osteomyelitis, and epidural abscess caused by Fusobacterium species and review the literature for patients with Fusobacterium spondylodiscitis.